Efforts to Increase the Income of Small Fishermen Through Off Fishing Employment in Banyuwangi Regency - Yusmia Widiastuti (Journal of Aquaculture Science, 2021)
AbstractThe utilization of fishery and marine resources in the form of fishing business in Banyuwangi Regency is still dominated by small-scale fisheries (traditional/small scale fisheries). It is known that there are still many fishing workers who depend on the fishermen for their livelihoods. So it is necessary to find alternative sources of additional income for small fishing households. The purpose of this study was to determine the economic behavior of fishermen's households, to analyze the contribution of off fishing businesses to the improvement of the fishermen's household economy, and to formulate alternative strategies to increase the income of fishermen's households in Banyuwangi Regency through off fishing employment. The research is focused on 2 sub-districts, namely Muncar District and Purwoharjo District, Banyuwangi Regency. The location selection was carried out by conducting a case study on small-scale fishing households that carried out an off-fishing business at the research location and 30% was taken using Simple Random Sampling. The analysis of the economic behavior of small fishermen households is described in the estimation of several variables of fishing experience, fishing frequency, number of fishing gear, boat size, and the addition of the amount of gasoline. The contribution of off-fishing businesses to the total household income of small-scale fishermen is quite varied, depending on the fishermen's income from fishing at sea. The greater the income of fishermen from catching fish in the sea, the greater the income of fishermen from catching fish at sea. By using the off fishing system, the strategy needed is the provision of technical training, especially regarding various fishery product processing to increase added value, institutional strengthening is carried out by making institutional reforms, and the problem of limited capital can be overcome by providing capital assistance.Keywords: economic behavior, income, strategy, off fishing